If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(y + 9) = 92 Reorder the terms: 7(9 + y) = 92 (9 * 7 + y * 7) = 92 (63 + 7y) = 92 Solving 63 + 7y = 92 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-63' to each side of the equation. 63 + -63 + 7y = 92 + -63 Combine like terms: 63 + -63 = 0 0 + 7y = 92 + -63 7y = 92 + -63 Combine like terms: 92 + -63 = 29 7y = 29 Divide each side by '7'. y = 4.142857143 Simplifying y = 4.142857143
| s-y=w | | 50-6*6= | | -5-6(3b+1)=39-8b | | -5x-6(x-5)=-x+30 | | 4(w+3)=8w | | 3x-11=x^2-9 | | D^2+8*d+9=0 | | 15-3*4= | | 4x^2-5=-5x+3 | | 3x+24y=9 | | -(8-4r)=-5+4r | | 24x^2+2xy-y^2=0 | | 23+5x=-2(x+6) | | 7(1+8v)+2v=7-6v | | 6(1-2x)-5=-83 | | 24x^2+2xr-r^2=0 | | 2x^3+x^2-19x+36=y | | -[2]=x-9 | | -2(v+3)=-18 | | x^2+1.68=2.6x | | 5(-4+m)=-45 | | 2x^3+x^2-19x+36=x | | -5r-3=-33 | | 6(4x+7)=105 | | 5(n+5)=34+8n | | f(x)=2x^3+x^2-19x+36 | | 3(x+2.5)=-7.5 | | x+6-2x-4=0 | | 9+3(2x-6)=14 | | -54=9n | | 6n-12=150 | | 3(x+2.5)=7.5 |